2020
DOI: 10.1155/2020/2621308
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Vitamin C Tends to Kill Colorectal Cancer with High MALAT1 Expression

Abstract: Background. Vitamin C (Vc) deficiency is frequently observed in cancer sites and has been proposed to have an antitumor effect. However, the mechanism of Vc’s killing effect is not clear. Besides, epigenetic alterations exhibit significant effects on colorectal cancer (CRC). This study aimed to explore the mechanism of Vc’s killing effect and its association to epigenetic alterations in CRC. Methods. Cell morphology, apoptosis, proliferation, and cycle were assayed to test Vc’s suppressive function in CRC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Prior studies for the effect of individual antioxidants on the development of CRC have been conducted, including vitamin A, vitamin C, vitamin E, selenium, manganese and zinc. Vitamins C and E are recommended to be protective agents against cancer 10‐13 . Minerals such as selenium, manganese and zinc are also considered to be essential elements in CRC prevention, 11,18,19 whereas several studies did not find a significant protective effect of vitamin A against the development of CRC 15‐17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies for the effect of individual antioxidants on the development of CRC have been conducted, including vitamin A, vitamin C, vitamin E, selenium, manganese and zinc. Vitamins C and E are recommended to be protective agents against cancer 10‐13 . Minerals such as selenium, manganese and zinc are also considered to be essential elements in CRC prevention, 11,18,19 whereas several studies did not find a significant protective effect of vitamin A against the development of CRC 15‐17 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamins C and E are recommended to be protective agents against cancer. [10][11][12][13] Minerals such as selenium, manganese and zinc are also considered to be essential elements in CRC prevention, 11,18,19 whereas several studies did not find a significant protective effect of vitamin A against the development of CRC. [15][16][17] A prospective cohort study reported an inverse relationship between high selenium intake and CRC risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same proves true for other dietary components, such as polyphenols [ 113 ] vitamins [ 114 , 115 , 116 ], and minerals [ 116 , 117 ] alone or in combination.…”
Section: Nutrients Epigenetics and Colorectal Cancermentioning
confidence: 72%
“…It has been found that high-dose Vitamin C administration has an inhibitory effect on MALAT1 and CRC metastasis [ 79 ].…”
Section: The Role Of Malat1 In Colorectal Cancermentioning
confidence: 99%